PELATIHAN PENGEMBANGAN TES DIAGNOSTIK KIMIA BAGI GURU KOTA DAN KABUPATEN MOJOKERTO UNTUK IDENTIFIKASI MISKONSEPSI SISWA - Novita, Dian; Suyono, Suyono; Yonata, Bertha; Rinaningsih, Rinaningsih; Delhita, Antina (Universitas Negeri Surabaya, 2026)
Chemistry is one of the fields of science that involves many concepts and is prone to misconceptions. This is because books, information from other people and the internet, misinterpreted experiences, and other sources provide inaccurate or incomplete information. Teachers are responsible for transferring knowledge or information and ensuring that the knowledge or information is understood correctly so that the teacher's ability to detect students' conception profiles becomes one of the competencies that teachers must have. Chemistry teachers in Mojokerto Regency and City need to map students' conceptions related to chemical concepts not only considering aspects of students' thinking skills. This is the basis for the community service team who have the initiative to provide training on Student Concept Mapping on Chemistry Material in Mojokerto Regency and City. The results obtained were that teachers' understanding of the development of diagnostic tests improved, from 57.14% to 88.09% and was proven by the preparation of diagnostic tests developed by teachers on acid-base, chemical bonds, and hydrocarbon materials. Keywords: training, mapping, chemical conception